Complex regulation of prolyl-4-hydroxylases impacts root hair expansion - Velásquez, Silvia Melina (2015)
Root hairs are single cells that develop by tip growth, a process shared with pollen tubes, axons, and fungal hyphae. However, structural plant cell walls impose constraints to accomplish tip growth. In addition to polysaccharides, plant cell walls are composed of hydroxyproline-rich glycoproteins (HRGPs), which include several groups of O-glycoproteins, including extensins (EXTs). Proline hydroxylation, an early post-translational modification (PTM) of HRGPs catalyzed by prolyl 4-hydroxylases (P4Hs), defines their subsequent O-glycosylation sites. In this work, our genetic analyses prove that P4H5, and to a lesser extent P4H2 and P4H13, are pivotal for root hair tip growth. Second, we demonstrate that P4H5 has in vitro preferred specificity for EXT substrates rather than for other HRGPs. Third, by P4H promoter and protein swapping approaches, we show that P4H2 and P4H13 have interchangeable functions but cannot replace P4H5. These three P4Hs are shown to be targeted to the secretory pathway, where P4H5 forms dimers with P4H2 and P4H13. Finally, we explore the impact of deficient proline hydroxylation on the cell wall architecture. Taken together, our results support a model in which correct peptidyl-proline hydroxylation on EXTs, and possibly in other HRGPs, is required for proper cell wall self-assembly and hence root hair elongation in Arabidopsis thaliana.